Does a Fourth Rus' Exist?: Concerning Cultural Identity in the Carpathian Region - Best, Paul J.; Stępień, Stanisław (Higganum, 2009)
Keywords: Europe, Eastern; Slavs; Slavs; United States; dept.psc; faculty_collection

Gentrification: The New Colonialism in the Modern Era - Wharton, Jonathan L. (Journal of the Oxford University Round Table: Forum on Public Policy, 2009)
Keywords: dept.psc; ⛔ No DOI found

Party change and the shifting dynamics in presidential nominations: the lessons of 2008 - Paulson, Arthur (Polity, 2009)
Presidential nominations in recent years have been settled with increasing speed, most of the time in the early stages of the primaries and caucuses, and certainly before the national convention, which has become more of a rally. Even when the battle for the Democratic Presidential nomination continued to the end of the primary season in 2008, it was settled before the convention. Analysts have emphasized the importance of the “invisible primary” and the front-loaded delegate selection schedule in explaining the early resolution of Presidential nomination contests. However, not enough attention has been paid to a much more fundamental change in our political parties and party system: The old umbrella parties have been replaced by ideological polarization between the parties and ideological homogenization within the parties. Our new party system dates back about forty years, and features increased ideological unity and decreased factionalism, making it easier to settle nominations. Even today's front-loaded nominating calendar would not have prevented some of the hotly contested conventions of the old umbrella parties. Polity (2009) 41, 312-330. doi:10.1057/pol.2009.4; published online 11 May 2009
Keywords: Elections; Nominations; Parties; Primaries; dept.psc

Late 19th century administrative reform in America: re-articulating Hamiltonian thought - O'Hara, Jonathan (International Review of Administrative Sciences, 2009)
In this article, the intellectual thought of a group of key late 19th century national administrative reformers is isolated and analyzed. These reformers were interested in reforming the civil, military and business administrative functions of the executive branch to provide for greater elite administrative supervision over and intervention in the national society and economy. The reformers often articulated their reform purposes, motives and goals in the Hamiltonian language of administrative authority and popular deference to executive administrative counsels. An important key to understanding this article is recognizing that while environmental social and economic conditions had changed significantly for the Gilded Age reformers since the American constitutional founding, many elements of the Hamiltonian tradition still resonated with the reformers a full century later. In this way, the historically transmitted ideology and rhetoric of Hamiltonian thought can be seen as having an independent, causative impact on the administrative reformers' purposes, motives and goals related to executive administrative reform.
Keywords: American founding; American progressivism; Developmental democracy; Gilded Age; Mugwumps; North America; United States; administrative reform; administrative system; bureaucracy; democracy; dept.psc; legal system; nineteenth century; planning process; political ideology

Real and imagined extremist threats in mexico and along the U.S.–Mexico border: ‘Colombianization’ as an antidote to leftist and criminal extremist networks - Olney, Patricia (Policing-an International Journal of Police Strategies & Management, 2009)
Keywords: dept.psc

The post Cold war reestablishment of effective state authority in Latin America: can 'colombianization' tame Mexico's security crisis? - Olney, Patricia (Social Science Research Network, 2009)
This paper explores the Post Cold War origins of the organized criminal violence that once gripped Colombia and now grips Mexico and particularly the highly controversial counterinsurgency strategy used in Colombia that forms the basis for the current strategy in Mexico. It argues that ideology is a reason why the military aspect of these problems was neglected for so long and the reason its detractors see it as a strategy that reduces national sovereignty and endangers democracy when statistics on control of territory, reduction of violence and democratic progress demonstrate the opposite to be true. The paper uses the term “colombianization” to emphasize Colombia’s dramatic shift from almost ungovernable to one of the most stable countries in the region. Colombianization is defined not as a counterdrug strategy as are both the Colombian and Mexican U.S. assistance strategies but as an integrated, law-based, counterinsurgency strategy implemented from the bottom up that facilitates the establishment of elite consensus and puts the country on a path toward rule of law. Ironically, it was democratic and free market reforms that strengthened the forces of instability in both Colombia and Mexico and the militarization of security that appears to facilitate democratic stability. This study uses local level assessments of Plan Colombia and local interviews conducted in Chihuahua and Michoacán to evaluate the prospects of colombianization in urban and rural Mexico. Colombia's experience suggests that colombianization can stabilize the country and help reactivate the economy but democratic progress is painfully slow and the strategy has little impact on the drug industry and the corruption associated with it.
Keywords: Patricia Olney; SSRN; The Post Cold War Reestablishment of Effective State Authority in Latin America: Can 'Colombianization' Tame Mexico's Security Crisis?; dept.psc; ⛔ No DOI found